1984
DOI: 10.1017/s0001566000007601
|View full text |Cite
|
Sign up to set email alerts
|

Twinning Rate by Month of Mother's Birth in Japan

Abstract: Records of two hospitals and of an association of mothers of twins were analysed for the years 1924-1980, finding a total of 656,109 and 1185 twin births, respectively. Twinning rates were higher in summer or fall, in general, but these seasonal variations occasionally changed within a short period of years, as in 1973-75 in the Association group. The twinning rate was also affected by the month of mother's birth. It was low among the mothers born around May-July in maternities up to 1960, and these mothers di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

1987
1987
1998
1998

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 12 publications
3
11
0
Order By: Relevance
“…In the present study, in agreement with the previous report [14], the mothers born in May-July did not show a peak of twinning in the summer-fall season, while the other mothers showed an excess in that season. To explain this phenomenon, we can also hypothesize immunogenic effeets of the above-mentioned seasonally epidemie factors.…”
Section: J F M a M J J A S O N D J Birth Monthsupporting
confidence: 94%
See 3 more Smart Citations
“…In the present study, in agreement with the previous report [14], the mothers born in May-July did not show a peak of twinning in the summer-fall season, while the other mothers showed an excess in that season. To explain this phenomenon, we can also hypothesize immunogenic effeets of the above-mentioned seasonally epidemie factors.…”
Section: J F M a M J J A S O N D J Birth Monthsupporting
confidence: 94%
“…This discrepancy from Weinberg's rule may not be explained until the zygosity of our UZ-LS twins is determined. The present analysis confirms the excess of twin births in the summer-fall season and its occasionai loss in agreement with our previous report [14]. It also shows that the years showing a summer-fall peak and the years showing no distinct seasonality appeared alternately in recent years.…”
Section: 6supporting
confidence: 93%
See 2 more Smart Citations
“…To our knowledge, this study is the first in which an association is found between month of birth and habitual miscarriage. Associations with month-of-birth have been described, though, for a great variety of features, among them several reproductive features such as early menarche (Jongbloet et al, 1994), menstrual disorders (Jongbloet et al, 1994), mean menstrual cycle length (Nakamura et al, 1987), twin proneness (Miura et al, 1984;Nonaka et al, 1993), and early and late menopause (Jongbloet et al, 1994).…”
Section: Discussionmentioning
confidence: 99%